Effect of Nitrogen Fixing Bacteria on Plant Growth and Yield of Brassica juncea - Ahmad, Irfan Khan*, Anwar Masood; Aquil (Journal of Phytology, 2010)
Brassica juncea (L.) Czern & Coss. is one of the major oilseed crops cultivated in India and around the world. The aim of this study was to evaluate the efficiency of Azotobacter, Azospirillum and their combination on plant growth and yield parameters of Brassica juncea cv. Varuna. A pot experiment was conducted in the net house of Department of Botany, G.F. (P.G.) College, Shahjahanpur (U.P.) to study the effect of two bacterial inoculations Azotobater, Azospirillun and their combination on growth and yield of Brassica juncea. Azotobacter and Azospirillum were applied separately and combination of both the bacteria in half doses. Application of both the bacteria recorded higher plant growth and yield in Brassica juncea. Azospirillum inoculation resulted in higher growth and yield parameters in comparison to Azotobacter inoculation. However, the combination of half dose of both the bacteria proved best in improving plant growth and yield in comparison to individual inoculation. Key words: Brassica juncea, Nitrogen fixing bacteria <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Irfan Khan et al. Effect of Nitrogen Fixing Bacteria on Plant Growth and Yield of Brassica juncea. J Phytol 2/9 (2010) 25-27.